Penggunaan Teknik Oscar Brocket (Olah Vokal dan Olah Tubuh) Dalam Meningkatkan Keterampilan Bermain Drama Peserta Didik Kelas XI.2 Sma Negeri 6 Palembang - Susanti, Retno Yunita; Lestari, Hikmah (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research aims to improve the drama playing skills of class XI.2 students at SMA Negeri 6 Palembang, in the vocal and physical aspects. The form of variable that was used as the target of change in this research was drama playing skills (aspects of vocal and physical exercise), while the action variable used was the use of Oscar Brocket's drama playing technique. This type of research is a form of the Kemmis and McTaggart model of classroom action research (PTK), which consists of 1 cycle in 1 meeting. Each cycle consists of planning stages, taking action, observing and reflecting. The subjects of this research were 32 students in class XI.2 SMA Negeri 6 Palembang. Data collection techniques use questionnaires, observation, interviews and documentation. The data analysis technique uses descriptive techniques supported by quantitative data from pre-action and post-action questionnaires. The results of the comparison of the average score of drama play practice in pre-action and post-action in cycle I of meeting I. The average score of pre-action drama play was 10.8 (43.2%), and the average score of drama play using the Oscar Brocket technique in the exercise aspect post-action vocal and physical exercise in cycle I, meeting I, amounted to 20.6 (80.25%). So it can be concluded that the provision of action in the form of the Oscar Brocket drama technique for vocal and body exercise for students in class.